Trunk posture tracking system with vibro-tactile feedback - Wee, Ming Xiao. (2013)
The aches and pains experienced by many are often a result of the long-term effects of distorted posture. Distorted posture is the posture that results from certain muscles tightening up or shortening while others lengthening or becoming weaker as a result of one's daily activities. One of the main reasons for distorted posture is incorrect sitting posture since one is in the sitting position most of the time. Hence, a trunk posture tracking system that can monitor and provide tactile feedback to users is developed to correct their sitting postures.